Thống kê hoạt động chất vấn tại Kỳ họp Quốc hội, phiên họp UBTVQH nhiệm kỳ Khóa XV - Tổng Thư ký Quốc hội (2022)
Toàn văn Thống kê hoạt động chất vấn tại Kỳ họp Quốc hội, phiên họp UBTVQH nhiệm kỳ Khóa XV